Chattering Attenuation Sliding Mode Approach for Nonlinear Systems. Issue 4 (1st February 2017) - Nemati, Hamidreza; Bando, Mai; Hokamoto, Shinji
Abstract: This study introduces a new robust nonlinear control scheme based on the theory of nonsingular terminal sliding mode control (NTSMC). Since conventional NTSMC utilizes a discontinuous switching function, a significant flaw called chattering can occur. The main purpose of this study is to design a new switching function based upon Lyapunov stability in order to alleviate this drawback over time. There are many approaches to mitigate the chattering drawback in SMC such as utilizing a smooth approximation of the switching element, or employing higher order sliding mode control (HOSMC) strategy. However, the use of a continuous approximation affects the system's performance and a finite reaching time to the sliding manifold, and in HOSMC the estimation of high‐order derivatives of states is usually difficult and it still exhibits chattering in the presence of parasitic dynamics. In this study by employing a new sliding manifold including a time function, the chattering is attenuated as well as keeping the robustness. Finally, a second‐order nonlinear dynamical system subject to disturbance is simulated to highlight the validity and applicability of the proposed method.